The First Intense Geomagnetic Storm Event Recorded by the China Seismo‐Electromagnetic Satellite - Y.‐Y. Yang; Z.‐R. Zhima; X.‐H. Shen; W. Chu; J.‐P. Huang; Q. Wang; R. Yan; S. Xu; H.‐X. Lu; D.‐P. Liu (Space Weather)
Abstract On 25 August 2018, the China Seismo‐Electromagnetic Satellite (CSES) encountered the first intense geomagnetic storm event since its launch on 2 February 2018. The main purpose of this work is to check in‐flight performance of the assembled payloads onboard CSES, as well as to investigate the ionosphere perturbations induced by this geomagnetic storm. The study shows that all investigated parameters simultaneously respond to the different phases of the geomagnetic storm, verifying the measuring capabilities of the assembled payloads onboard CSES. Specifically, the magnetic field obtained from the high‐precision magnetometer fits well with that obtained by the Swarm satellite, clearly demonstrating the development phase of the storm; joint analysis using the Langmuir probe, plasma analyzer, electric field detector, and GNSS occultation receiver data demonstrate that this is a positive storm event and that electric field penetration is the possible mechanism for the disturbance in the ionosphere. During this storm event, some significant ELF/VLF waves are also excited and there is enhancement of the energetic electron flux (of energy <1 MeV). These main features are consistent with results from previous works, indicating the excellent performance of the search coil magnetometer and high‐energy particle detector.